2021
DOI: 10.1038/s41467-020-20447-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a subset of immunosuppressive P2RX1-negative neutrophils in pancreatic cancer liver metastasis

Abstract: The immunosuppressive microenvironment that is shaped by hepatic metastatic pancreatic ductal adenocarcinoma (PDAC) is essential for tumor cell evasion of immune destruction. Neutrophils are important components of the metastatic tumor microenvironment and exhibit heterogeneity. However, the specific phenotypes, functions and regulatory mechanisms of neutrophils in PDAC liver metastases remain unknown. Here, we show that a subset of P2RX1-negative neutrophils accumulate in clinical and murine PDAC liver metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 66 publications
1
64
0
Order By: Relevance
“…Moreover, increased C5aR1 + neutrophils were linked to tumor progression and poor survival for BC patients. Similarly, a recent study identifies a unique neutrophil subclone that lacks P2RX1 and participates in immunosuppression and cancer metastasis [ 25 ]. These studies indicate that the characterization of different neutrophil subsets based on specific molecules can guide the development of neutrophil-targeting precision therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased C5aR1 + neutrophils were linked to tumor progression and poor survival for BC patients. Similarly, a recent study identifies a unique neutrophil subclone that lacks P2RX1 and participates in immunosuppression and cancer metastasis [ 25 ]. These studies indicate that the characterization of different neutrophil subsets based on specific molecules can guide the development of neutrophil-targeting precision therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigating development of liver metastases also analysed transcriptomic responses by neutrophils to cytokines. Mouse bone marrow neutrophils were stimulated with G-CSF, as well as lipopolysaccharide, interferon Ī³ and IL-4 [117] and analysed by RNAseq. Wang and colleagues only reported differential expression of 19 genes for purinergic receptors dependent upon the stimulating cytokine [117].…”
Section: Cancermentioning
confidence: 99%
“…Recent studies showed that liver metastatic PDAC contains exhausted CTLs, suggesting that targeting the immunosuppressive TME could be a promising strategy for treating liver metastasis of PDAC [6,8]. In the paper by Wang et al [1], the immunosuppressive TME in PDAC liver metastasis was found to be due mainly to the activity of a subset of neutrophils deficient in the purinergic receptor P2RX1 that accumulated in the presence of PDAC metastasis. Neutrophils are a critical component of the TME, with both antitumoural and protumoural activities.…”
Section: Commentarymentioning
confidence: 99%
“…However, in latestage cancers, this immune population displayed potent antitumour properties [9]. P2RX1-deficient neutrophils infiltrating PDAC liver metastasis facilitate the creation of an immunosuppressive microenvironment, inhibiting CTLs responses [1,10]. This subset of neutrophils up-modulate expression on their surface of immune escape and N2-like molecules, such as PD-L1, and reprogram their metabolism by switching towards an oxidative-mitochondrial metabolism that supports their immunosuppressive features.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation